2021
DOI: 10.1177/2167702621994545
|View full text |Cite
|
Sign up to set email alerts
|

Physical Distancing and Mental Health During the COVID-19 Pandemic: Factors Associated With Psychological Symptoms and Adherence to Pandemic Mitigation Strategies

Abstract: In this epidemiological investigation, we assessed the prevalence of depression and anxiety symptoms during the COVID-19 pandemic. A total of 10,061 adults participated in the study. Symptoms of depression and anxiety were 2 to 3 times higher compared with prepandemic samples. Participants who predominantly socially distanced themselves revealed substantially higher symptoms than their counterparts. Females, ethnic and sexual-orientation minorities, younger adults, unemployed individuals, and participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
130
1
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 59 publications
10
130
1
7
Order By: Relevance
“…The results may be explained by the adverse effects of social isolation, the economic recession, and disruptions in mental health care services due to the pandemic 1,2 . The results are in line with research on adults showing substantial increases in mental health problems among adults early in the pandemic [14][15][16][17][18] . However, the increase of about 2.13 units on a scale from 0 to 100 shows that the effect is of a moderate magnitude and seems to be considerably smaller than what has been found in studies on adults.…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 89%
See 2 more Smart Citations
“…The results may be explained by the adverse effects of social isolation, the economic recession, and disruptions in mental health care services due to the pandemic 1,2 . The results are in line with research on adults showing substantial increases in mental health problems among adults early in the pandemic [14][15][16][17][18] . However, the increase of about 2.13 units on a scale from 0 to 100 shows that the effect is of a moderate magnitude and seems to be considerably smaller than what has been found in studies on adults.…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 89%
“…In the domain of mental health, it has been suggested that the pandemic leads to increasing mental health problems in children and adolescents because of the unique combination of social isolation, economic recession, and disruptions in mental health care services for adolescents 1,2 . Moreover, large-scale studies in several countries have indicated that early in the pandemic, mental health problems increased among adults [14][15][16][17][18] . However, research on adolescents has not been conclusive.…”
Section: Previous Research On the Impact Of The Pandemic On Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in a study comparing mental health during the onset of the pandemic in Norway, Germany, and four other countries [41]. Prevalence of mental distress was higher in another Norwegian large-scale investigation that was carried out when all COVID-19 regulations were in force, and that was based on a sample with predominantly young adults [57]. Still, both the Norwegian and German-speaking samples presented here revealed degrees of mental distress that are higher than those reported in general population samples before the COVID-19 pandemic [47,[58][59][60].…”
Section: The Study Samples In the Context Of Covid-19 Mental Distress Researchsupporting
confidence: 80%
“…At the first wave of data collection (i.e., between March 31 and April 7, 2020), 10 061 participants were recruited through an online survey disseminated via national, regional, and local information platforms (i.e., television, radio, and newspapers), in addition to dissemination to a random selection of Norwegian adults through a Facebook Business algorithm. This procedure is elaborated in detail elsewhere (Ebrahimi et al, 2021). All respondents were re-contacted for participation for the fourth wave of data collection between January 23 to February 2, 2021, of which 4571 were eligible for the present study.…”
Section: Participants and Proceduresmentioning
confidence: 99%